2023
DOI: 10.1371/journal.pone.0288997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of turmeric (Curcuma longa) supplementation on glucose metabolism in diabetes mellitus and metabolic syndrome: An umbrella review and updated meta-analysis

Thanika Pathomwichaiwat,
Peerawat Jinatongthai,
Napattaoon Prommasut
et al.

Abstract: Aims This study aims to comprehensively review the existing evidence and conduct analysis of updated randomized controlled trials (RCTs) of turmeric (Curcuma longa, CL) and its related bioactive compounds on glycemic and metabolic parameters in patients with type 2 diabetes (T2DM), prediabetes, and metabolic syndrome (MetS) together with a sub-group analysis of different CL preparation forms. Methods An umbrella review (UR) and updated systematic reviews and meta-analyses (SRMAs) were conducted to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
(263 reference statements)
0
4
1
Order By: Relevance
“…The results may be attributed to the antihyperglycaemic property of C. longa, its antioxidant and anti-inflammatory properties. Poor glycaemic control, oxidative stress, dyslipidemia and inflammation have been linked to anxiety-like behavior and C. longa might have acted through its effect on blood glucose levels, antioxidant enzyme activities, inflammation and dyslipidemia (Ahmad et al, 2020;Sharifi-Rad et al, 2020;Ovaditya et al, 2022;Pathomwichaiwat et al, 2023). These findings disagree with our previous findings where a high percentage (20% C. longa supplementation) increases anxiety-like behavior in normoglycaemic animals (Garkuwa et al, 2021).…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…The results may be attributed to the antihyperglycaemic property of C. longa, its antioxidant and anti-inflammatory properties. Poor glycaemic control, oxidative stress, dyslipidemia and inflammation have been linked to anxiety-like behavior and C. longa might have acted through its effect on blood glucose levels, antioxidant enzyme activities, inflammation and dyslipidemia (Ahmad et al, 2020;Sharifi-Rad et al, 2020;Ovaditya et al, 2022;Pathomwichaiwat et al, 2023). These findings disagree with our previous findings where a high percentage (20% C. longa supplementation) increases anxiety-like behavior in normoglycaemic animals (Garkuwa et al, 2021).…”
Section: Resultscontrasting
confidence: 63%
“…It was shown to improve glucose metabolism (Uchio et al, 2022), reduce fasting blood glucose levels (Pathomwichaiwat et al, 2023), glycaemic control and reduce the formation of advanced glycation end products among type-2 diabetic individuals (Abbas et al, 2022). Hyperglycemia has been the major driver of oxidative stress, inflammation and dyslipidemia (Hasheminasabgorji and Jha, 2021;Tangvarasittichai, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG-HPMA-DL and PEG-HPMA-Bz were synthesized and characterized using 1 H NMR spectroscopy and gel permeation chromatography as described previously [33]. The 1 H NMR spectra were recorded using a Gemini 300 MHz spectrometer (Varian Associates Inc. NMR Instruments, Palo Alto, CA, USA), using d 6 -DMSO as a solvent and the DMSO peak at 2.50 ppm was used as the reference line. Gel permeation chromatography was performed using two serial PLgel 5 µm MIXED-D columns (Polymer Laboratories).…”
Section: Preparation Of Polymeric Micellesmentioning
confidence: 99%
“…Many reports have shown that curcumin possesses anti-diabetic activity [5]. Curcumin supplementation can significantly reduce fasting blood glucose and hemoglobin A1C levels and other metabolic parameters in type 2 diabetes [6,7]. An in vitro study on cancer cell lines demonstrated that curcumin can inhibit cell-cycle progression and metastasis through many signaling pathways [8].…”
Section: Introductionmentioning
confidence: 99%